Emotional Intelligence (EQ) Profile of Gifted Students Engaged in E-Sport - Muhammad Shafiq Zakuan Shahrulnaim; Muhammad Danish Zaquan Mohd Nazri; Ahmad Fuad Mohamad Amin; Nurul Atikah Anuar (Kolej PERMATA Insan, 2025)
Insan Junior Researcher International Conference & Innovation (iJURECON) 2025 : “STREAM for a Better Future/ editor : Ahmad Fuad Mohamad Amin, Nurul Shazwani Binti Mohamed, Rossidi Bin Usop, Abdel Rahman Ibrahim Suleiman Islieh Organised by Kolej PERMATA Insan 10-11 October 2025